FEASIBILITY ANALYSIS OF 1MW SOLAR POWER PLANT IN KADUNA POLYTECHNIC MAIN CAMPUS USING RET SCREEN SOFTWARE - Pindiga, Ismaila Yusuf; Muhammad, S. U; Mohammed, M. A.; Zarmai, M. T. (FUDMA Journal of Sciences, 2025)
High electricity consumption and the resulting costs are significant challenges for managing public tertiary institutions in Nigeria. As a result, the utility companies frequently disconnect many institutions from the grid to force them to settle their debts .Facilities such as laboratories, libraries, and hostels have constant power demands. Electricity needs are met through power supplied by the Kaduna Electric distribution company, with institutions paying according to tariffs set by regulators and agreed upon by the utility. The proposed solution aims to lower electricity costs at Kaduna Polytechnic’s main campus wshile reducing the carbon footprint, making the campus more sustainable. The analysis focuses on electricity generation, reducing greenhouse gas emissions, and financial aspects, using RET Screen simulation software. Weather data from NASA’s database was export to analyses the performance of the photovoltaic system, 1MW solar power plant is recommended for installation at the campus. The results show that using RET Screen software, benchmark analysis, carbon emission reduction, and financial impacts can be effectively evaluated. The study reveals that the energy production cost is reduced to 0.12/kWh, with a greenhouse gas emission reduction of 639.2t CO2. Additionally, the system would export 1.5672 MWh of electricity to the national grid, generating an annual revenue of NGN 154,173,000 for the institution, with a simple payback period of 11.8 year.The aim of this study is to encourage public institutions to explore solar power as an independent energy source, addressing energy shortages and contributing to the development of sustainable energy infrastructure in Nigeria’s higher education institutions